2023
DOI: 10.3390/ijms241612809
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Epidermal-Melanin-Unit: The Human Scalp Anagen Hair Bulb Is Home to Multiple Melanocyte Subpopulations of Variable Melanogenic Capacity

Abstract: The visual appearance of humans is derived significantly from our skin and hair color. While melanin from epidermal melanocytes protects our skin from the damaging effects of ultraviolet radiation, the biological value of pigmentation in the hair follicle, particularly on the scalp, is less clear. In this study, we explore the heterogeneity of pigment cells in the human scalp anagen hair follicle bulb, a site conventionally viewed to be focused solely on pigment production for transfer to the hair shaft. Using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…In the present study, scRNA-seq analysis revealed 12 candidate melanocyte markers, including NPY, GPNMB, SYP, TSPAN10, ROPN1L, CA2, GSTA3, SOX10, PTPN5, GSTO2, GSTA2 , and RAC2 . Among them, GPNMB ( Li et al, 2023b ), TSPAN10 ( Xi et al, 2020 ), ROPN1L ( Mazzio and Soliman, 2018 ), SOX10 ( Casalou et al, 2023 ), and RAC2 ( Liu et al, 2023 ) have been reported to be closely associated with melanin-related biological processes. They participate in the development of various diseases by influencing melanin-related physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, scRNA-seq analysis revealed 12 candidate melanocyte markers, including NPY, GPNMB, SYP, TSPAN10, ROPN1L, CA2, GSTA3, SOX10, PTPN5, GSTO2, GSTA2 , and RAC2 . Among them, GPNMB ( Li et al, 2023b ), TSPAN10 ( Xi et al, 2020 ), ROPN1L ( Mazzio and Soliman, 2018 ), SOX10 ( Casalou et al, 2023 ), and RAC2 ( Liu et al, 2023 ) have been reported to be closely associated with melanin-related biological processes. They participate in the development of various diseases by influencing melanin-related physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that there were several attempts made to search for appropriate TAAs as targets in melanoma cells. Analyses comparing protein expression between skin and uvea melanomas indicate tumor antigens like tyrosinase, melan-A, and SOX10 [18,[85][86][87]. Another useful marker for distinguishing cell phenotypes (spindle from epithelioid) in skin melanomas, like p75NTR, is not appropriate in UM spindle cell identification.…”
Section: Cell-based Immunotherapiesmentioning
confidence: 99%
“…However, unequivocal characteristics of cancer stem cells in UM are not confirmed. An additional difficulty in the identification of UM TAA antigens is the internal differentiation of tumor cells, as observed in cutaneous melanomas or hair follicles, where expression of the antigens characteristic of melanosomes changes together with the differentiated and undifferentiated states of these cells [87,94]. Despite the above difficulties, clinical trials using CAR-T therapy (NCT03635632) against inter alia uveal melanoma are ongoing.…”
Section: Cell-based Immunotherapiesmentioning
confidence: 99%